Tectonic development of the North Patagonian Andes and their related Miocene foreland basin (41°30'-43°S) - Orts, Darío Leandro (2012)
The Northern Patagonian Andes have been constructed through multiple mechanisms that range from tectonic inversion of extensional structures of Early to Middle Jurassic age in the Main Andes to Oligocene in the Precordilleran region. These have acted during two distinctive orogenic stages, first in late Early Cretaceous and later in Miocene times Late Oligocene extension separates these two contractional periods and is recorded by half-grabens developed in the retroarc region. The last contractional stage coexists with an eastward foreland expansion of the late Miocene arc whose roots are presently exposed as minor granitic stocks and volcanic piles subordinately in the Main Andes, east of the present arc. As a consequence of this orogenic stage a foreland basin has developed, having progressed from 18 Ma in the main North Patagonian Andes, where the mountain front was flooded by a marine transgression corresponding to the base of the irihuau Formation, to 11 Ma in the foreland area. Cannibalization of this foreland basin occurred initially in the hinterland and then progressed to the foreland zone. Blind structures formed a broken foreland at the frontal zone inferred from growth strata geometries. During Pliocene to Quaternary times most of the contractional deformation was dissipated in the orogenic wedge at the time when the arc front retracted to its present position.